(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess the dynamics of optical coherence tomography (OCT) and OCT angiography (OCTA) retinal and choroidal morphological and morphometric changes in post-COVID-19 patients depending on the angiotensin-converting enzyme (ACE) gene variant. Methods: The study included 104 post-COVID-19 patients (208 eyes). We evaluated OCT and OCTA retinal and choroidal morphological and morphometric changes in patients who had recovered from COVID-19 with various courses. Patients were imaged with the RTVue XR 100 Avanti OCT. We examined the distribution of ACE (rs 4340) genotypes among 94 patients. A molecular and genetic study of ACE gene (rs4340) variants was carried out using allele-specific polymerase chain reaction. We analyzed possible correlations between retinal and choroidal morphological and morphometric changes in post-COVID-19 patients and ACE gene variants. Results: In post-COVID-19 patients, we found reductions (p < 0.001) over time in macular retinal thickness and choroidal subfoveal thickness and increases overtime in foveal avascular zone (FAZ) area, superficial capillary plexus (SCP) vessel density, and deep capillary plexus (DCP) vessel density. II, ID and DD ACE genotypes were found in 29.6%, 50.5%, and 19.9%, respectively, of the 94 patients. There were statistically significant correlations (р < 0.001) of the ACE DD genotype with an increase in FAZ area, SCP vessel density, and DCP vessel density, and a reduction in choroidal subfoveal thickness at 12 months after recovery from COVID-19. Conclusion: We found statistically significant correlations (р < 0.001) of the ACE DD genotype (but not the ACE II or ID genotype) in post-COVID-19 patients with retinal and choroidal morphological and morphometric changes; these changes indicate that the retina and choroid suffered hypoxia in the post-COVID-19 period. OCT and OCTA are non-invasive biomarkers of an early vascular dysfunction after SARS-CoV-2 infection. The risk of developing retinal and choroidal morphological and morphometric changes in post-COVID-19 patients with the ACE II or ID genotype was lower (p = 0.001) compared to patients with the ACE DD genotype.